Post-COVID 19 Tourism Recovery and Resilience: Thailand Context - Wongmonta, Seri (International Journal of Multidisciplinary in Management and Tourism, 2021)
COVID 19 is a pandemic that has great impacts on tourism businesses. All countries are relying on vaccination to create herd immunity, so that they can open their doors to welcome international tourists. It is important to build confidence in health and hygiene in order to create tourism demands after COVID 19. The use of social media is another necessary strategy to communicate stories of attractions and tourism resources of a destination. Other than marketing strategies to operate tourism businesses, the “new normality”, strategies on safety protocols and sanitary measures are also important factors that every business in the tourism industry must regard them mandatory. The government must implement and communicate adequate health and safety protocols at all points of the travel journey. To fully reopen doors to international arrivals and travelers could travel freely with less fears of contracting COVID 19, worldwide immunization programs must have been completed to make sure that there is a herd immunity in place. Tourism recovery and resilience must be carried out along with confidence through health safety and security measures. Principles of community-based tourism and sustainable tourism must be observed. Travel recovery and resilience must enhance livelihoods and economies with responsibility and sense of solidarity. The government must provide economic packages to entrepreneurs for tourism recovery and resilience.